A first record of complete mitochondrial genome of Cryptalaus Ohira (Insecta: Coleoptera: Elateridae) based on C. yamato (Nakane). Issue 1 (2nd January 2019) - Lee, Seung-Gyu; Choi, Subin; Roh, Seung Jin; Lee, Bong-Woo; Lim, Jongok
Abstract: A complete mitochondrial DNA genome of a rare click beetle, Cryptalaus yamato (Nakane), is the first reported. The genome consists of 15, 882 base pairs including 13 protein-coding genes (PCGs), 20 tRNAs, two rRNAs, and a 1279 bp long AT-rich region. The overall base composition is 69.4% AT and 30.6% GC. The maximum likelihood analysis based on nucleotide sequence data of 13 PCGs supported that C. yamato is involved in monophyletic group of Elateridae.